Performance of Islamic Unit Trusts during the 2007 Global Financial Crisis: Evidence From Malaysia - Salina H. Kassim; Saqinah Kamil (Asian Academy of Management Journal, 2012)
By focusing on the Malaysian Islamic unit trusts over the period of January 2000 to December 2009, this study attempts to analyse the performance of the Islamic unit trusts in various economic conditions; during a crisis period and non-crisis period. The adjusted Sharpe index, adjusted Jensen Alpha index, and Treynor index are adopted to compare the performance of the Islamic unit trusts against the market benchmark and risk-free return. In measuring risk and diversification, the study relies on the standard deviation and R2 coefficient of determination, respectively. The findings reveal that during the non-crisis period, the performance of the Islamic unit trusts is comparable to that of the market benchmark, while during the crisis period, the Islamic unit trusts perform better compared to the non-crisis period. These findings suggests that the Islamic unit trust funds can be an ideal hedging instrument during a down market and provide potential portfolio diversification benefits for the investors. Based on these findings, the investors could strategize and diversify their portfolio accordingly during different market conditions.